Non-equilibrium heating path for the laser-induced nucleation of metastable skyrmion lattices. Issue 42 (20th September 2022) - Olleros-Rodríguez, Pablo; Strungaru, Mara; Ruta, Sergiu; Gavriloaea, Paul-Iulian; Gudín, Adrián; Perna, Paolo; Chantrell, Roy; Chubykalo-Fesenko, Oksana
Abstract : We demonstrate the possibility of field-free, ultrafast creation of topologically protected nanoscale magnetic skyrmions in ferromagnets via single-pulse laser excitation, holding the promise for the next-generation of memory and logic devices. Abstract : Understanding formation of metastable phases by rapid energy pumping and quenching has been intriguing scientists for a long time. This issue is crucial for technologically relevant systems such as magnetic skyrmions which are frequently metastable at zero field. Using Atomistic Spin Dynamics simulations, we show the possibility of creating metastable skyrmion lattices in cobalt-based trilayers by femtosecond laser heating. Similar to the formation of supercooled ice droplets in the gas phase, high temperature ultrafast excitation creates magnon drops and their fast relaxation leads to acquisition and quenching of the skyrmion topological protection. The interplay between different processes corresponds to a specific excitation window which can be additionally controlled by external fields. The results are contrasted with longer-scale heating leading to a phase transition to the stable states. Our results provide insight into the dynamics of the highly non-equilibrium pathway for spin excitations and pave additional routes for skyrmion-based information technologies.